"Jump in Any Time": How Teacher Struggle with Curricular Reform Generates Opportunities for Teacher Learning. (3rd May 2017) - Peercy, Megan Madigan; Martin-Beltrán, Melinda; Yazan, Bedrettin; DeStefano, Megan
ABSTRACT: With the emergence of new academic demands created by curricular reforms such as the Common Core State Standards (CCSS), policy makers and educators have recognized that the linguistic complexity of new curricula requires greater coordination of instructional efforts in teaching English language learners (ELLs). However, the literature has yet to explore what such collaborative efforts look like in classroom settings as teachers engage in teaching new curricula to diverse learners. In this qualitative study, we examine the collaborative interaction and learning of one fourth grade teacher and her English for speakers of other languages (ESOL) colleague as they implemented their district's new CCSS-based English/language arts curriculum. The authors found that the teachers' work simultaneously involved struggle and opportunity for learning as they engaged with new curricular demands. Findings from this study point to the need for further research into teachers' collaborative practices around curriculum reform as opportunities for situated teacher learning.